1984
DOI: 10.1063/1.333572
|View full text |Cite
|
Sign up to set email alerts
|

New material for permanent magnets on a base of Nd and Fe (invited)

Abstract: A new compound composed of Nd, Fe, and a small quantity of B about 1 weight has been found, which has a tetragonal structure with lattice constants a = 0.880 nm and c = 1.221 nm. This phase, which has the approximate composition, 12 atom Nd, 6 atom B and balance Fe, possesses remarkable magnetic proper ties. From the approach to saturation an anisotropy con stant of about 3.5 MJ/m 3 can be calculated, while satura tion magnetization amounts to 1.35 T. The magnetiza tion versus temperature curve shows a Curie t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
625
1
18

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,732 publications
(710 citation statements)
references
References 5 publications
12
625
1
18
Order By: Relevance
“…Its particles were composed of nanocrystalline grains of the Nd 2 Fe 14 B phase, having a mean size of around 30 nm. The theoretical density of the Nd-Fe-B powder was 7.51 g/cm 3 .…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Its particles were composed of nanocrystalline grains of the Nd 2 Fe 14 B phase, having a mean size of around 30 nm. The theoretical density of the Nd-Fe-B powder was 7.51 g/cm 3 .…”
Section: Methodsmentioning
confidence: 96%
“…It has also been reported that HE can be successfully applied to processes of consolidation of hard magnetic powders [2], however, powder metallurgy is still the most commonly used method of powder densification [3]. The undoubted advantage of HE is the very short time of the extrusion, and tri-axial state of stress, continuously acting at the billet during the entire process of hydrostatic extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…For higher force and energy density, neodymium permanent magnets are generally selected because of their outstanding magnetic properties [26]. From a microfabrication and ease of assembly perspective, the use of magnetic materials that can be directly deposited in a batch fabrication process might be appealing.…”
Section: Magnet Dimensions and Magnetizationmentioning
confidence: 99%
“…Sintered Nd-Fe-B permanent magnets have been widely used due to their excellent magnetic properties [1][2][3]. The increasing demand has resulted in the enormous production of Nd-Fe-B magnets.…”
Section: Introductionmentioning
confidence: 99%